Multiplicité des cadres de protection des Droits de l’Homme (2008)
This article is a research result of the Group of Properties, which is part of the work undertaken within the project on the influence of the inter-American system in the Colombian constitutional law.The protection of human rights since the Second World War has generated a growing and scatteredproduction of these rights’ control tools and frameworks, whose effects have been little studied underthe light of the systematic nature of law. This article aims to identify the tools that have been developedon the subject, by analyzing each of the aspects of this phenomenon, without losing sight of the ultimategoal of the entire system: the protection of the human person. The article is built as a dissertationaccording to the french method, and is part of the work that the author sent to the Institute of InternationalStudies at the University of Paris II.